2010
DOI: 10.1068/a42151
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Structure and Productivity in US Metropolitan Areas

Abstract: Recent concepts as megaregions and polycentric urban regions emphasize that external economies are not confined to a single urban core, but shared among a collection of close-by and linked cities. However, empirical analyses of agglomeration and agglomeration externalities so-far neglects the multicentric spatial organization of agglomeration and the possibility of 'sharing' or 'borrowing' of size between cities. This paper takes up this empirical challenge by analyzing how different spatial structures, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
264
4
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(290 citation statements)
references
References 49 publications
16
264
4
6
Order By: Relevance
“…Perhaps polycentric metropolitan areas (areas where borrowed size would be especially likely to occur) are characterised by a special balance between agglomeration benefits and costs. Meijers and Burger (2010) show that in the U.S. urban system this balance is better in polycentric metropolitan areas than in those areas dominated by a large city. Interestingly, some scholars have suggested that agglomeration costs are confined more to the city boundaries than the spatial range of agglomeration benefits (Parr, 2002).…”
Section: Balance Of Agglomeration Benefits and Costsmentioning
confidence: 99%
“…Perhaps polycentric metropolitan areas (areas where borrowed size would be especially likely to occur) are characterised by a special balance between agglomeration benefits and costs. Meijers and Burger (2010) show that in the U.S. urban system this balance is better in polycentric metropolitan areas than in those areas dominated by a large city. Interestingly, some scholars have suggested that agglomeration costs are confined more to the city boundaries than the spatial range of agglomeration benefits (Parr, 2002).…”
Section: Balance Of Agglomeration Benefits and Costsmentioning
confidence: 99%
“…Some cities have a monocentric spatial distribution, and some are polycentric in distribution, therefore, the spatial form is different [10]. Although urban spatial form varies, most researchers divide urban spatial form into two types: scattered spatial form and polycentric spatial form [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Developing more suitable measurements of functional integration of MCRs is not only relevant on its own terms (MEIJERS, 2008), but also because research on polycentric development serves as the input to broader research questions altogether. MEIJERS and BURGER (2010), for instance, have shown how different spatial structures -and in particular the monocentricity /polycentricity dimension -affect the economic performance of metropolitan areas. Here we focus on the three above-mentioned issues, and tackle these by (i) introducing an alternative approach to measure polycentricity based on actual transaction link data, (ii) developing an alternative method to calculate the FPI, and (iii) extending the conceptualization of functional polycentricity by introducing a formal model to test the degree of urban network integration.…”
Section: Introductionmentioning
confidence: 99%